2019
DOI: 10.1111/gec3.12441
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing qualitative GIS research—Toward a wider usage of open‐source GIS and reproducible research practices

Abstract: Geographic Information Systems (GIS) have become an indispensable tool in all fields dealing with geographic data in academia as well as the public and private sector. After some initial reservations, human geography and other social sciences have also embraced GIS technologies especially by extending and adjusting the available data models for qualitative data. The result was coined qualitative GIS. Given the diversity and fragmentation of the research in which qualitative GIS have been applied, a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
(65 reference statements)
0
16
0
1
Order By: Relevance
“…Using systematic analysis based on a rubric for reproducible research, we found that the majority of AGILE papers neither provided sufficient information for a reviewer to evaluate the code and data and attempt a reproduction, nor enough material for readers to reuse or extend data or code from the analytical workflows. This is corroborated by research in related disciplines such as quantitative geography [3], qualitative GIS [21], geoscience [16], and e-Science [10]. The problems identified in these related research areas are transferable to the scientific discipline of GIScience, which operates at the intersections of aforementioned fields [11].…”
Section: Introductionmentioning
confidence: 75%
“…Using systematic analysis based on a rubric for reproducible research, we found that the majority of AGILE papers neither provided sufficient information for a reviewer to evaluate the code and data and attempt a reproduction, nor enough material for readers to reuse or extend data or code from the analytical workflows. This is corroborated by research in related disciplines such as quantitative geography [3], qualitative GIS [21], geoscience [16], and e-Science [10]. The problems identified in these related research areas are transferable to the scientific discipline of GIScience, which operates at the intersections of aforementioned fields [11].…”
Section: Introductionmentioning
confidence: 75%
“…Free and open source statistical software and visualization packages have been developed and adopted in scientific communities (Lowndes et al, 2017;Hampton et al, 2015;Lausch et al, 2015) and are replacing commercial software like in case of R and Python shared under a GNU license (Hampton et al, 2015). For spatial data management using geographic information system (GIS), free and open source software such as QGIS, GRASS GIS, and SAGA GIS are widely used (Muenchow et al, 2019;Rocchini et al, 2017); there is accordingly less need for expensive commercial GIS software. The codes specific for GHG community are now also shared openly (like in case of EddyProhttps://www.licor.com/env/support/EddyPro/software.html or the ONEFlux tool described by Pastorello et al, 2020).…”
Section: Free Open Source Software Data and Computational Resourcesmentioning
confidence: 99%
“…Statistical software and visualization packages have been developed and adopted in scientific communities 260 (Lowndes et al, 2017;Hampton et al, 2015;Lausch et al, 2015) like in case of R and Python that are used and shared under a GNU license (Hampton et al, 2015). The same is valid for GIS open source software such as QGIS, GRASS GIS, and SAGA GIS (Muenchow et al, 2019;Rocchini et al, 2017) and for codes specific for GHG community that are now also shared openly (like in case of EddyPro-https://www.licor.com/env/support/EddyPro/software.html or the ONEFlux tool described by Pastorello et al, 2020). 265…”
Section: Access To Data Software and Computational Resourcesmentioning
confidence: 99%